Patient Satisfaction of Outpatient Department Services in a Level 1 Private Hospital in Western Visayas, Philippines - Divinagracia, Sheryl S.; Guevarra, Joseph G. (Philippine Social Science Journal, 2025)
This study assessed patient satisfaction with outpatient department (OPD) services at a level 1 private hospital, aiming to assess satisfaction across various aspects (doctors, nurses, access, appointments, and facilities) based on patient demographics and visit frequency. Using a quantitative descriptive-comparative design and a modified patient satisfaction questionnaire, data was collected from 385 OPD patients aged 18 and above via quota and convenience sampling. Results showed overall satisfaction with doctors, nurses, access, and appointments, but dissatisfaction with facilities. Patient satisfaction also significantly differed based on family monthly income, though not by sex, age, educational attainment, frequency of visit, or number of OPD services availed. These findings highlight the need for facility improvements and equitable healthcare access, providing actionable insights for hospital administrators and policymakers to enhance service quality and patient experience. Future research could expand to multiple hospitals, incorporate more variables, utilize mixed-methods, and employ longitudinal designs for deeper understanding.